The Effect of Corporate Social Responsibility and an Emphasis on the Sustainability of the Environment on Small and Medium-Sized Businesses’ Ecological Sustainability: The Role of Green Capabilities as a Mediator - Yang, Wenshu; Hwang, Yong-Sik (Journal of Ecohumanism, 2024)
Purpose: – Recent studies indicate that manufacturers Small and Medium Enterprises (SMEs) have become increasingly conscious of problems with the environment. Manufacturing companies play a crucial role in minimizing the adverse consequences of the changing climate through the implementation of sustainable practices and creating eco-friendly products. Few studies have concentrated on the concept of Corporate Social Responsibility (CSR) for issues related to the environment, despite the fact that CSR is currently a mainstream topic in global business regulation and is frequently used to validate an organization’s financial results and image as a business. Method: A questionnaire for surveys is used in this study for collecting data from 570 CEOs of Small and Medium-Sized Businesses (SMEs) in China. Evaluation of information and testing of assumptions are done with structural equation modelling. Analysis: As evidenced by the present findings, ECSR increases EEP and GPDP. Consequently, in order to improve their overall performance in green management and attain sustainable management objectives, companies need to adopt the promotion of ECSR. Conclusion: Consequently, in order to improve their general efficiency in green management and attain sustainable management, businesses need to put into practice the promotion of ECSR. This research adds to the body of knowledge on environmental management and offers recommendations on how practitioners can improve organizational capacities to handle environmental problems through creative environmental campaigns.